2010
DOI: 10.1007/s00011-010-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lazaroid U-74389G in a rat sepsis model

Abstract: Lazaroid treatment of E. coli-inoculated septic animals lessens the hemodynamic deterioration seen in sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moreover, short term pre-exposure of healthy subjects to EPI before injection of low-dose endotoxin decreased the secretion of the pro-inflammatory cytokine TNF-α and stimulated the production of the anti-inflammatory IL-10 [31]. In our previous study [2], the concentrations of IL-6 and TNF-α were the highest 2 hours after E. coli inoculation in immunocompromised rats and then subsequently www.bjbms.org decreased at 6 hours, while IL-1β levels stayed approximately the same. In the current study, the concentrations of TNF-α, IL-1β, and IL-6 were all higher after LPS intravenous infusion in rats, peaking at 2 hours.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Moreover, short term pre-exposure of healthy subjects to EPI before injection of low-dose endotoxin decreased the secretion of the pro-inflammatory cytokine TNF-α and stimulated the production of the anti-inflammatory IL-10 [31]. In our previous study [2], the concentrations of IL-6 and TNF-α were the highest 2 hours after E. coli inoculation in immunocompromised rats and then subsequently www.bjbms.org decreased at 6 hours, while IL-1β levels stayed approximately the same. In the current study, the concentrations of TNF-α, IL-1β, and IL-6 were all higher after LPS intravenous infusion in rats, peaking at 2 hours.…”
Section: Discussionmentioning
confidence: 76%
“…In our previous study [2], we demonstrated that the concentrations of the inflammatory mediators IL-6 and TNF-α were the highest 2 hours after Escherichia coli (E. coli) inoculation in irradiated immunocompromised rats and subsequently were decreased at 6 hours; on the contrary, IL-1β levels stayed approximately the same at all time points examined. Both major HRV components, LF and HF, were decreased during the early hyperdynamic phase after bacteria inoculation.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…U-74389G has been clinically developed as a potential drug to protect against ischemia/ reperfusion injury of the central nervous and liver, but did not achieve regulatory approval [11,12]. The use of antioxidants in inflammatory diseases has been widely advocated and studies suggested that U-74389G and other 21-aminosteroids are potent inhibitors of the synthesis of several pro-inflammatory cytokines, such as IL-6, IL-8, interferon-g (IFN-g) and tumor necrosis factor-a (TNF-a) [13,14].…”
Section: Introductionmentioning
confidence: 99%